Routine opioid outcome monitoring in community pharmacy: Pilot implementation study protocol - Nielsen, S.; Kowalski, M.; Wood, P.; Larney, S.; Bruno, R.; Shanahan, M.; Lenton, Simon; Dietze, P.; Green, T.; Murnion, B.; Ritter, A. (Elsevier, 2018)
Increases in opioid use and related harms such as mortality are occurring in many high income countries. Community pharmacists are often in contact with patients at risk of opioid-related harm and represent an ideal point for intervention. Best practice in monitoring opioid-related outcomes involves assessing analgesia, pain functioning, mood, risks and harms associated with opioid use. Community pharmacists are well-placed to undertake these tasks. Objectives: Our pilot study will test the implementation of a computer-facilitated screening and brief intervention (SBI). The SBI will support pharmacist identification of opioid-related problems and provide capacity for brief intervention including verbal reinforcement of tailored information sheets, supply of naloxone and referral back to the opioid prescriber. The SBI utilises software that embeds study procedures into dispensing workflow and assesses opioid outcomes with domains aligned with a widely accepted clinical framework. Methods: We will recruit and train 75 pharmacists from 25 pharmacies to deliver the Routine Opioid Outcome Monitoring (ROOM) SBI. Pharmacists will complete the SBI with up to 500 patients in total (20 per pharmacy). Data will be collected on pharmacists’ knowledge and confidence through pre- and post-intervention online surveys. Data on feasibility, acceptability and implementation outcomes, including naloxone supply, will also be collected. Project impact: Our study will examine changes in pharmacists’ knowledge and confidence to deliver the SBI. Through the implementation pilot, we will establish the feasibility and acceptability of a pharmacist SBI that aims to improve monitoring and clinical management of patients who are prescribed opioids.